The Nutrition of the Rabbit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Edited by C de Blas and J Wiseman. 1998. 352 pp. ISBN 0 85199 279 x£55 / h 78.50 Published by CABI Publishing Wallingford, Oxon OX10 8DE, UK Fax: +44 1491 829292